Textural/structural, stability and morphological properties of mesostructured silicas (MCM-41 and MCM-48) prepared using different silica sources - Gaydhankar, T. R.; Taralkar, U. S.; Jha, Ratnesh Kumar; Joshi, P. N.; Kumar, R (Catalysis Communications, 2005)
A series of MCM-41 and MCM-48 samples have been synthesized under hydrothermal and static conditions using different silica sources (fumed silica, silica sot and ethyl silicate) and characterized by powder XRD, scanning electron microscopy and N-2 adsorption. The silica source reactivity trend observed was as: ethyl silicate > fumed silica > silica sot. However, the extent of contraction caused by calcination, magnitude of the wall thickness and stability were found to depend not only upon the type of silica source used but also on the type of structure formed. Noticeable morphological differences were observed in case of only MCM-41 when silica sources were varied. © 2005 Elsevier B.V. All rights reserved.

Structural evolutions of hydrothermally prepared mesostructured MCM-48 silica using differently manufactured amorphous silica powders - Taralkar, U. S.; Jha, Ratnesh Kumar; Joshi, P. N. (Journal of Non-Crystalline Solids, 2007)
The hydrothermal synthesis of Si-MCM-48 mesoporous molecular sieves was carried out using a ternary SiO2:CTAOH:H2O System wherein differently manufactured amorphous silica powders such as fumed silica (FMDS), spray dried precipitated silica (SDPS) and flash dried precipitated silica (FDPS) were used as silica source materials. The changes in structural/textural properties were evaluated using powder XRD, N-2 adsorption-desorption and scanning electron microscopy techniques. Studies on the progressive development of MCM-48 mesophases revealed that, the reactivity of the silica source follow the trend: FMDS > SDPS > FDPS. MCM-48 synthesized using low cost FDPS has exhibited thicker pore walls but poorer orderness, while MCM-48 prepared from relatively expensive FMDS has thinner pore walls and more ordered structure. Moreover, the extent of contraction caused by calcinations, agglomerate size and structural stability were found to depend on the reactivity of the silica source used. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: long-range order; micelles; scanning electron microscopy; silica; silicates; sol-gels (xerogels); X-ray diffraction

Influence of synthesis conditions on structural properties of MCM-48 - Taralkar, U. S.; Kasture, M. W.; Joshi, P. N. (Journal of Physics and Chemistry of Solids, 2008)
The influence of synthesis variables such as time, cetyltrimethyl ammonium hydroxide (CTAOH) concentration, water content, pH, temperature and silica source on the structural properties of Si-MCM-48 is investigated. Time-dependent studies on the progressive development of MCM-48 have indicated that synthesis time is a crucial parameter, which influences the unit cell parameter. The formation of different mesophases was observed when the concentration of CTAOH and pH of the initial gel were varied. The Si-29 MASNMR results showed that the (Q(2) +W-3)/Q(4) ratio decreases with the increase in synthesis temperature. On account of increase in W units at high-temperature synthesis run, Si-MCM-48 with highly polymerized silica walls with lower surface area was obtained when compared with Si-MCM-48 prepared at lower temperature. Such effect was not significant when Si-MCM-48 was synthesized at the same temperature but using silica sol as a source in place of fumed silica. (c) 2008 Elsevier Ltd. All rights reserved.

Synthesis, characterization and catalytic performance of Sn-MCM-48 in solvent-free Mukaiyama-type aldol condensation reactions - Taralkar, U. S.; Kalita, Pranjal; Kumar, Rajiv; Joshi, P. N. (Applied Catalysis A-General, 2009)
The influence of various synthesis variables on the physico-chemical properties of mesoporous stannosilicate molecular sieves with MCM-48 structure (Sn-MCM-48) has been investigated. Sn-MCM48 has been used as a new heterogeneous catalyst in solvent-free Mukaiyama-type aldol reactions. Invariably, the beta-hydroxy ester selectivity was found to be 100% irrespective of the conversion level. The product yield was found to increase, to reach a maximum (70%), and then to decrease with the increase in tin content. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Characterization; heterogeneous catalysis; Hydrothermal synthesis; Mesoporous molecular sieves; Mukaiyama-aldol condensation; Sn-MCM-48

Synthesis of Si-MCM-41 from ternary SiO2-CTAOH-H2O system via dry gel conversion route - Taralkar, U. S.; Niphadkar, P. S.; Joshi, P. N. (Journal of Sol-Gel Science and Technology, 2009)
Steam assisted dry gel conversion method was employed for the synthesis of Si-MCM-41 from ternary SiO2:CTAOH:H2O systems wherein fumed silica was used as a source of silica. The influence of synthesis time, molar ratios of CTAOH/SiO2 in dry gel and the water content at the bottom of autoclave on the quality and formation of mesophases has been investigated. Powder XRD, N-2 adsorption-desorption, TEM and hydrothermal stability test were the techniques used for sample characterization. Keeping molar ratio of CTAOH/SiO2 constant, shorter synthesis time, lower unit cell parameter and d spacing were observed when steam assisted dry gel conversion method was employed in place of conventional hydrothermal method. There exists an optimum lower limit for water content at the bottom of autoclave for reducing the synthesis period. Keeping synthesis temperature and CTAOH/SiO2 molar ratio fixed, Si-MCM-41 with improved hydrothermal stability was obtained by steam assisted dry gel conversion route.
Keywords: Dry gel conversion; powder diffraction; Si-MCM-41; Sol-gel growth; Structural stability; Textural properties